HUBUNGAN ANTARA PENDIDIKAN IBU DENGAN KEMAMPUAN IBU DALAM MENSTIMULASI PERKEMBANGAN PSIKOSOSIAL OTONOMI PADA TODDLER - Esti Widiani (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2018)
Toddlers are the second stage of psychosocial development after babies in the age range of 18 months to 36 months. To avoid failure in passing through the stages of psychosocial development, autonomy versus doubt or shame need to provide good stimulation. The purpose of this study was to determine the relationship of mothers education with the ability of mothers to stimulate psychosocial development of autonomy in children. This study uses an observational design with a cross sectional approach. The study was conducted in the Kemantren Village, Jabung District, Malang Regency. The technique used for sampling in this study is accidental sampling with the number of samples obtained were 168 respondents. The instrument used to measure mother's ability is a modification from Infant-Toddler Child Care HOME Inventory. The data analysis used was spearman rank with a statistically significant correlation between maternal education and mother's ability to stimulate the development of psychosocial autonomy with p = 0,000 (p <0.005). The BKB (Toddler Family Development) group is recommended to be held in each Posyandu as a service center and learning center for mothers who conduct early detection and developmental stimulation.